Pengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Kepuasan Kerja Di Pesantren Darul Muttaqin - Muhammad Hilmy Muda Ramadhan; Muhammad Aziz Firdaus; Widhi Ariyo Bimo3 (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
In research entitled the influence of the work environment and work stress on job satisfaction at the Darul Muttaqien Islamic Boarding School, with a sample size of 52 respondents. The method used is a questionnaire research instrument distributed to employees and processed using a computer application. This research was carried out at the Bogor Dhuafa Wallet Integrated Health Hospital. Environmental variables (X1) and work stress (X2) on job satisfaction (Y) were processed using regression analysis, t test, f test, and coefficient of determination. The results of this research show that the work environment variable (X1) and the work stress variable (X2) have an effect on job satisfaction (Y) and motivation and the work environment have a joint effect on employee performance.